Insight into functional tricuspid valve regurgitation pathogenesis, pathological stages, and surgical management. (1st September 2021) - Sarraj-Asil, Anas; Diez-Villanueva, Pablo
Abstract: The tricuspid valve has generally been ignored, and considered as a "second class structure" in cardiac valve surgery. Tricuspid valve regurgitation is considered "functional" in over 70% of cases, generally produced by pulmonary hypertension secondary to left heart diseases in the context of an anatomically normal tricuspid valve apparatus. Many questions and doubts persist regarding to the pathogenesis of so-called functional tricuspid valve regurgitation. This article reviews the interfering factors in the function of the tricuspid valve to better identify the entity of the term "functional" and clarify its different pathological stages including the surgical procedures recommended in each stage. Highlights: TA dilatation depends on predisposing factors, whereas TV tethering depends on RV resistance against trigger factors. Transcatheter tricuspid procedures could be a reasonably good option for symptomatic high-risk patients with isolated TR. A successful and durable repair of TR requires an individual and detailed analysis of the mechanisms of TR, as well as the implementation of surgical techniques recommended for each stage.